Assessing Adaptive Capability of English Teachers in Implementing Differentiated Instruction Models in Selected Junior High Schools in Mataram - Henny Soepriyanti; Untung Waluyo; Eka Fitriana; Hartati Suryaningsih; Refa Andini (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
The study addresses the recurrent difficulties teachers experience in response to curriculum reforms that require flexibility, creativity and technology use to respond to heterogeneous student populations. With a qualitative multi case study as its design, the research involved fifteen English teachers of five junior high schools who had applied the Merdeka Curriculum for at least one year. Methods Data were obtained through in-depth interviews and classroom observations as well as documents analysis to ensure validity and reliability. Results indicate a wide discrepancy in teachers’ adaptative capacities, depending on the access to professional formation, technological preparedness and institutional support. More flexible teachers were found to design creative approaches in adapting content, process and product for meeting the learning profiles of students. Others had limited facilities, no motivation and minimal parental participation. However, despite these barriers, most of the teachers demonstrated a positive attitude and ongoing efforts toward self-improvement through self-study and peer support. Adaptive teaching is identified in the study as also crucially for achieving the aims of Merdeka Curriculum and therefore there should be ongoing (contextual) teacher training that supports reflective practice and differentiated pedagogy.